PEMANFAATAN SISTEM INFORMASI UNTUK PENGELOLAAN DATA KOPERASI SIMPAN PINJAM MENGGUNAKAN VISUAL BASIC - Dendy Kurniawan; Elva Sutrisna (Pusat Riset dan Inovasi Nasional, 2023)
Information System for Savings and Loans Cooperatives Using Visual Basic Case Studies at the Semarang Regency Regional Employment Agency is an information system created to overcome data processing problems which are still in the form of manual bookkeeping and even there is no evidence of deposit transactions, loans and installments and existing storage can be overcome by creating an information system for processing data on savings and loan cooperative transactions and creating a more secure and efficient data storage information system. Savings and loan information system design methods are made using R&D, Flowchat, DFD, ERD, and Normalization methods. The program used to create this application uses the Microsoft Visual Basic 6.0 programming language and MySQL as database management. The results of this study indicate that the savings and loan cooperative information system that is applied in the Savings and Loans Cooperative of the Semarang Regency Regional Civil Service Agency can be used to process member data, process savings data, process loan data, process data that has been paid off, process SHU distribution data, and make reports. finances safely and efficiently.